1987
DOI: 10.1001/archderm.1987.01660250091026
|View full text |Cite
|
Sign up to set email alerts
|

The Skin Changes in the Crow-Fukase (POEMS) Syndrome

Abstract: A man with a six-year history of intermittent burning sensations in his legs, hypothyroidism, and peripheral neuropathy also had hypertrichosis, hyperpigmentation, Terry nails, and taut thickened skin of the extremities. Discovery of a plasma cell tumor led to recognition of the Crow-Fukase syndrome, and appropriate treatment with melphalan and prednisone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Nerve fiber lesions were studied in about 120 cases. There was segmental demyelination alone in six of 17 cases ( Nakanishi et al, 1984 ) and in the case described by Shelley and Shelley (1987) , and axonal degeneration alone was described in three of 17 cases ( Nakanishi et al, 1984 ) , in two of four cases ( Saida et al, 1997 ) , in the two cases reported by Teixeira et al (1990) , and in 12 individual cases ( Trentham et al, 1976 ; Iwashita et al, 1977 ; Bitter et al, 1985 ; Berkovic et al, 1986 ; Semble et al, 1986 ; Reulecke et al, 1988 ; Barrier et al, 1989 ; Donaghy et al, 1989 ; Romas et al, 1992 ; Orefice et al, 1994 ; Simmons et al, 1994 ; Midroni and Bilbao, 1995 ) . A mixture of segmental demyelination and axonal degeneration was found in 73 cases: eight of 17 cases ( Nakanishi et al, 1984 ) , nine cases ( Ohnishi, 1984 ) , six cases ( Pareyson et al, 1994 ) , 22 cases ( Vital et al, 1994 ) , seven cases ( Watanabe et al, 1998 ) , four cases ( Adams and Said, 1998 ) , two cases ( Ohi et al, 1985 ; Gherardi et al, 1988 ; Saida et al, 1997 ) , and 11 individual cases ( Driedger and Pruzanski, 1980 ; Bourdette and Rosenberg, 1984 ; Hyman and Westrick, 1986 ; Lapresle et al, 1986 ; Semble et al, 1986 ; Viard et al, 1988 ; Brousolle et al, 1991 ; Crisci et al, 1992 ; Adelman et al, 1994 ; Tuite and Bril, 1997 ; Adams et al, 2000 ) .…”
Section: Discussionmentioning
confidence: 92%
“…Nerve fiber lesions were studied in about 120 cases. There was segmental demyelination alone in six of 17 cases ( Nakanishi et al, 1984 ) and in the case described by Shelley and Shelley (1987) , and axonal degeneration alone was described in three of 17 cases ( Nakanishi et al, 1984 ) , in two of four cases ( Saida et al, 1997 ) , in the two cases reported by Teixeira et al (1990) , and in 12 individual cases ( Trentham et al, 1976 ; Iwashita et al, 1977 ; Bitter et al, 1985 ; Berkovic et al, 1986 ; Semble et al, 1986 ; Reulecke et al, 1988 ; Barrier et al, 1989 ; Donaghy et al, 1989 ; Romas et al, 1992 ; Orefice et al, 1994 ; Simmons et al, 1994 ; Midroni and Bilbao, 1995 ) . A mixture of segmental demyelination and axonal degeneration was found in 73 cases: eight of 17 cases ( Nakanishi et al, 1984 ) , nine cases ( Ohnishi, 1984 ) , six cases ( Pareyson et al, 1994 ) , 22 cases ( Vital et al, 1994 ) , seven cases ( Watanabe et al, 1998 ) , four cases ( Adams and Said, 1998 ) , two cases ( Ohi et al, 1985 ; Gherardi et al, 1988 ; Saida et al, 1997 ) , and 11 individual cases ( Driedger and Pruzanski, 1980 ; Bourdette and Rosenberg, 1984 ; Hyman and Westrick, 1986 ; Lapresle et al, 1986 ; Semble et al, 1986 ; Viard et al, 1988 ; Brousolle et al, 1991 ; Crisci et al, 1992 ; Adelman et al, 1994 ; Tuite and Bril, 1997 ; Adams et al, 2000 ) .…”
Section: Discussionmentioning
confidence: 92%
“…Although POEMS syndrome is well described in the medical literature, 1–4,15,16 most information regarding its skin findings is from isolated case reports or small case series 17–20 . To take advantage of our institution’s experience with a large series of patients, we sought to determine the prevalence and characteristics of cutaneous manifestations on diagnosis of POEMS syndrome and to identify correlations between these skin findings and other clinical manifestations of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Various plasma cell proliferative disorders such as plasmacytoma, Crow-Fukase syndrome, and idiopathic plasmacytic lymphadenopathy (IPL) have also been reported to respond well to melphalan therapy (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%